Inverse nodal problem for p–laplacian dirac system. (31st August 2016) - Gulsen, Tuba; Yilmaz, Emrah; Koyunbakan, Hikmet
Abstract : In this study, we solve an inverse nodal problem for p ‐Laplacian Dirac system with boundary conditions depending on spectral parameter. Asymptotic formulas of eigenvalues, nodal points and nodal lengths are obtained by using modified Prüfer substitution. The key step is to apply modified Prüfer substitution to derive a detailed asymptotic estimate for eigenvalues. Furthermore, we have shown that the functions r(x) and q(x) in Dirac system can be established uniquely by using nodal parameters with the method used by Wang et al. Obtained results are more general than the classical Dirac system. Copyright © 2016 John Wiley & Sons, Ltd.